The Effect of Existing Soil on the Unconfined Compressive Strength (UCS) Value on Cement Treated Recycling Base (CTRB) Type Flexible Pavement - Suratno; Iphan F. Raddam; Yasruddin (Global Writing Academica Researching & Publishing, 2023)
Recycling technology or Cement Treated Recycling Base (CTRB) is one method for repairing damage to ancient road pavements, however, when the process is in place (Mixed in place), difficulties can arise, such as mixing with existing soil material that shouldn't be mixed in its implementation. because this will affect the results of Unconfined Compressive Strength (UCS). As a binder in the form of local cement from South Kalimantan, the brand is cheaper because production costs are cheaper. This study aims to obtain UCS Results at minimal cement levels that still meet the requirements with the use of brand local cement, obtain the typical influence of existing soil on UCS and what percentage of existing soil material can still be tolerated either curing or non-curing and correlation and get recommendations for the maximum percentage of influence of percent of existing land on UCS in curing or non-curing conditions. RAM samples were obtained for the purpose of investigation, which was done in a lab, existing soil and additional materials in the field. Inspection of old aggregates, making test specimens with variations in cement content of 1-10%, after obtaining minimum UCS according to technical requirements then making test specimens with variations in soil examinations and soil content of 0%, 5%, 10%, 15%, 20%, and 25% again then conducting data analysis to find correlations / relationships. The results of the research showed variances in cement content of 1% (one) - 10% that still meet the technical specifications of UCS (at least 30 kg/cm²) obtained a minimum cement content of 5% (five percent) with a UCS of 33.77 kg/cm². Then the test results of the influence of existing soil on UCS that is still tolerated are mixed, namely in curing conditions is 17% with the equation Y = -0.10075 x + 46.894 (R2 = 0.964). and non-curing 8.9% with the equation Y = -0.1113 x + 39.814 (R2=0.956). The R2 conclusions for both indicate a very There is a substantial correlation between the two factors